Engaging faith communities in public health messaging in response to COVID-19: Lessons learnt from the pandemic in Ituri, Democratic Republic of Congo - Amuda Baba; Amuda Baba; Liz Grant; Nigel Pearson; Emma Wild-Wood; Jean-Benoit Falisse; Yossa Way; Sadiki Kangamina (Frontiers Media S.A., 2022)
PurposeTo understand challenges faced by faith leaders in the Democratic Republic of Congo (DRC) in engaging with current public health strategies for the COVID-19 pandemic; to explain why long-standing collaborations between government, faith-based health services and leaders of faith communities had little impact; to identify novel approaches to develop effective messaging that resonates with local communities.MethodsA qualitative participatory research design, using a workshop methodology was deployed to seek opinions of an invited group of faith leaders in the DRC provinces of Ituri and Nord-Kivu. A topic guide was developed from data gathered in prior qualitative interviews of faith leaders and members. Topics were addressed at a small workshop discussion. Emerging themes were identified.FindingsLocal faith leaders described how misinterpretation and misinformation about COVID-19 and public health measures led to public confusion. Leaders described a lack of capacity to do what was being asked by government authorities with COVID-19 measures. Leaders' knowledge of faith communities' concerns was not sought. Leaders regretted having no training to formulate health messages. Faith leaders wanted to co-create public health messages with health officials for more effective health messaging.ConclusionPublic trust in faith leaders is crucial in health emergencies. The initial request by government authorities for faith leaders to deliver set health messages rather than co-develop and design messages appropriate for their congregations resulted in faith communities not understanding health messages. Delivering public health messages using language familiar to faith communities could help to ensure more effective public health communication and counter misinformation.